Violation of human rights in the face of natural disasters in Perú - Sánchez Tarrillo, Segundo Juan (2020)
The essay aims to analyze the vulnerability of human rights to natural disasters in Peru. By its nature, the techniques of the office were used and the deductive method was used for the analysis. The results reveal the violation and protection of rights, as well as the appropriate actions to prevent certain risks before, during and after emergencies due to the indifference of the authorities and the passivity and irresponsibility of the community. It is concluded that the vulnerability of Human Rights to disasters is the total suppression of economic, social and gender inequalities that already exist in society before the natural event and consequently the mitigation of the deepening of these problems after the event. natural event.